Assessment of the impact of age on DIBH in radiotherapy based on the prospective GATTUM and B-REST trials - Rebecca Moser; Lena Marie Buchecker; Jantje M. Bohlen; Mathias Düsberg; Maximilian Aigner; Nina A. Mayr; Jana Nano; Sophie T. Behzadi; Sophia Kiesl; Marciana-Nona Duma; Markus Oechsner; Stephanie E. Combs; et al. (Clinical and Translational Radiation Oncology)
Background: Adjuvant radiotherapy (RT) of left sided breast cancer is increasingly performed in deep inspiration breath hold (DIBH). This technique requires active involvement and compliance of patients as well as pulmonary endurance. Since previous studies focused on female patients with a median age under 65 years to test practicability of DIBH and advantages in comparison to free breathing (FB), DIBH in elderly patients over 65 years remains mostly underexplored. This study aims to evaluate attitudes and feasibility of DIBH in elderly breast cancer patients. Methods: First a 14-item survey of 100 female breast cancer patients aged ≥65 years was conducted to assess their attitudes toward DIBH and their breath-hold capability. Secondly, we performed a matched-pair analyses using pooled data from the prospective GATTUM and B-REST trials to compare respiratory and dosimetric parameters during DIBH between patients aged ≥65 years (n = 30) and <65 years (n = 30). Results: According to the survey large majority of patients were interested in DIBH: 98 % stated that age should not be a criterion when selecting patients for DIBH, and 66 were able to hold their breath > 20 s. Based on the matched-pair analyses of the GATTUM and B-Rest trials, no significant differences were observed regarding breath hold amplitude, duration and stability, and in DIBH-induced dose reduction to organs at risk between elderly (≥65) (n = 30) and younger patients (n = 30). Conclusion: Based on our results age alone should not be used as a criterion for excluding patients from DIBH in the treatment of left-sided breast cancer.